Decolonizing Heteronormative Conceptions on Gender and Sexual Identity: Investigating Through an Indigenous Lens - Jenner, Ginger (Scholarship@Western, 2021)
Internalized racism, oppression, stigma, and discrimination that exists within the Indigenous lesbian, gay, bisexual, transexual, and individuals who question their gender or sexual identity (LGBTQ+ two spirit) community, are under-researched compared to their nonIndigenous counterparts. Current western research models and theories do not adequately account for the biopolitical roots of the social and structural determinants of health that the Indigenous LGBTQ+ two-spirit experience and are limited in their explanations of the structural violence they suffer. I argue that we need to better understand, from a biopolitical and biopower perspective, how the colonial history that Indigenous peoples have endured has altered Indigenous conceptions of gender and/or sexual identity. Furthermore, I will argue that the revitalization of Anishinaabe gikendaasowin (Anishinaabe knowledge), rejuvenation of Anishinaabe izhitwaanin – (Anishinaabe culture), and perspective on gender, is critical to understanding the Indigenous LGBTQ+ two-spirit community for biskaabiiyang (returning back to ourselves). https://ir.lib.uwo.ca/headandheartprogram_2021/1005/thumbnail.jpg